Load-velocity slope can be an indicator of the active drag in front crawl swimming - Gonjo, T.; Ljødal, I.; Karlsson, R.; Olstad, B. H. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to investigate the relationship between swimming load-velocity slope and the active drag (Da) in front crawl. 19 female and 22 male swimmers were recruited and performed three 25 m front crawl sprints with different external loads (1, 3, 5 kg for females and 1, 5, and 9 kg for males) assigned by a robotic resistance device. The mean swimming velocity was plotted against the external load to establish the load-velocity profile for each swimmer. Da was obtained by the velocity perturbation method. The relationship between the load-velocity slope and Da was assessed using the Pearson correlation coefficient, which showed a very large correlation (r = 0.84, p < 0.001) and an extremely large correlation (r = 0.93, p < 0.01) for female and male swimmers, respectively, indicating that the load-velocity slope is an indicator of Da in front crawl swimming.